Paradigma Baru Hukum Pidana Dalam Menangani Kejahatan Digital Lintas Batas Negara - Andrean Nurhakim; Ahmad Fauzan; Milkan Sibawaeh (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2025)
The development of information technology has given rise to transnational forms of digital crime and poses serious challenges to national criminal law systems. Digital crime is no longer bound by a specific time and place, thus weakening the effectiveness of the conventional criminal law paradigm based on the principle of territoriality. This study aims to analyze the need for a renewed criminal law paradigm in addressing transnational digital crime and to formulate a criminal law policy direction that is more adaptive to global and digital realities. This study uses normative legal research methods with conceptual, statutory, and comparative approaches. The analysis examines criminal law doctrine, jurisdictional principles, and regulatory developments and law enforcement practices related to transnational cybercrime. Data were obtained through a literature review sourced from scientific literature, international journals, and relevant legal documents related to digital crime and transnational legal cooperation. The results of the study indicate that the national and territorial criminal law paradigm is no longer adequate to address the complexity of transnational digital crime. A new, transnational criminal law approach is needed, emphasizing legal harmonization, strengthening proportional extraterritorial jurisdiction, and effective international cooperation. This study confirms that updating the criminal law paradigm is a primary prerequisite for ensuring legal certainty, effective law enforcement, and protection of human rights in the global digital era.